More than "potential offenders" : understanding adults who are sexually attracted to children who have not offended : thesis submitted in partial completion of the requirements for the degree of Doctor of Clinical Psychology, Massey University, Albany - Muir, Sophie A. (Massey University, 2018)
There has been recent recognition that pedophilia has largely been studied and addressed in the context of child sex offending. Using a qualitative-dominant mixed method design, this study explores what it is like to live with an attraction to children for those who are non-offending, how such individuals manage their attraction, and what support needs they have. The experiences of nine minor-attracted men as captured in semi-structured interviews were analysed. Through an interpretive phenomenological analysis, five themes were identified: ‘A Sexual Attraction to Children’, ‘Stigma and Identity Distress’, 'Disclosure’, ‘Strategies for Living Well’, and, ‘Vision for Change’. In addition to this, demographic and descriptive data collected in online surveys with 85 minor-attracted persons were computed. Overall, participants experienced their attraction to children as complex, with challenges that included making sense of their attraction as a sexual orientation, living with distress, and the public vilification of people with pedophilia. Drawing from individual strengths, behavioural strategies, and peer resources, participants described coping with distress and managing their sexual behaviour. In light of their abilities to regulate their sexual attractions, participants did not necessarily perceive themselves to be at risk of child sex offending. Participants expressed a need for greater support options for minor-attracted persons and approaches to support that are not founded on stereotypical understandings of minor-attraction. This would recognise that minor-attracted persons who have not offended are not simply “potential offenders” but are human beings who can be prosocial and wish to be accepted in society.
Keywords: Pedophilia; Sexual attraction; Sexual desire disorders; Child sexual abuse; Prevention